Collaborative Governance in Sustainable Forestry Management in the Era of Regional Autonomy Amidst the Threats of Deforestation and Climate Change - Musmuliadi; Ida Bagus Made Agung Dwijatenaya (Global Research Collaboration, 2026)
Sustainable forest management has become a critical issue in Indonesia due to increasing deforestation, climate change, and the challenges associated with regional autonomy. This study aims to examine the role of collaborative governance in promoting sustainable forest management within the context of decentralized governance. A mixed methods research design was employed, integrating qualitative and quantitative approaches to provide a comprehensive understanding of forest governance practices. Qualitative data were collected through semi-structured interviews, observations, and document analysis involving local governments, community representatives, environmental organizations, and other relevant stakeholders. Quantitative data were obtained from secondary sources related to forest cover change, deforestation rates, and environmental indicators. The findings reveal that collaborative governance significantly contributes to improving forest management effectiveness through enhanced stakeholder participation, institutional coordination, transparency, and shared responsibility. Local communities play a crucial role in conservation efforts, particularly when supported by inclusive policies and strong institutional frameworks. The study also finds that regional autonomy provides opportunities for more responsive and context-specific forest governance; however, challenges such as limited institutional capacity, resource constraints, and stakeholder conflicts remain significant barriers. Furthermore, successful sustainable forest management is influenced by political commitment, community participation, institutional capacity, and trust among stakeholders. The study concludes that strengthening collaborative governance mechanisms and fostering multi-stakeholder partnerships are essential for addressing deforestation and climate change while ensuring long-term forest sustainability. These findings provide valuable insights for policymakers and practitioners seeking to improve forest governance and environmental sustainability in Indonesia.